CONTRIBUTION OF OFFLINE AND ONLINE TRAVEL AGENT TOWARD ROOM OCCUPANCY AT FOUR POINTS BY SHERATON BALI SEMINYAK HOTEL - Putu Septiawan; Nyoman Mastiani Nadra; Ni Nyoman Sri Astuti (Journal of Applied Sciences in Travel and Hospitality, 2018)
The background of this research was based on of technology development that affect to room sales at Four Points by Sheraton Bali Seminyak. Room sales and promotion are made through offline and online travel agent. The purpose of this research to determine the level contribution of offline and online travel agent toward room occupancy of Four Points by Sheraton Bali Seminyak and to determine the highest contribution of offline and online travel agent. The data was collect by observation, interview and documentation. The data source were used are Primer and secondary data and the type of data were used quantitative data. The data will analyzed used descriptive statistic, the processing using Microsoft Excel to analyzed data by descriptive statistic function mean, median, modus, standard deviation. Based on calculation the contribution of offline and online travel agent was dominate by Expedia with total contribution by 61,78% and Coorendon with total contribution by 37,71% on 2015-2017. The suggestion could be given that the hotel should to strengthen in relationship with travel agent and make good contract rate and offer the best package for their market., so that the travel agent could provide the great contribution toward room occupancy of Four Points by Sheraton Bali Seminyak Hotel.